Design, Characterization And Molecular Docking Of Isatin Derivative - D., Jadhav Monali; P., Jatte Kalleshvar; N., Naik Sachin; M., Munale Bhagyashri; K., Mali Kiran; A., Nalawade Rutuja; P., Pulate Chetan (Journal of Neonatal Surgery, 2025)
Isatin (2,3-dioxindole) is an important class of heterocyclic compounds, isatin derivatives are synthetically important substrates, which can be used for many synthesis of a large variety of heterocyclic compounds, and as raw material for drug synthesis. Recently, isatin derivatives have attracted strong interest in organic and medicinal chemistry due to their potent biological and pharmacological activities